Enterococcal bacteremia is associated with prolonged stay in the medical intensive care unit - Viju Moses; Jayakumar Jerobin; Anupama Nair; Sowmya Sathyendara; Veeraraghavan Balaji; Ige Abraham George; John Victor Peter (Journal of Global Infectious Diseases, 2012)
Background: Although enterococci are relatively common nosocomial pathogens in surgical intensive care units (ICUs), their significance in blood cultures from patients in the medical ICU is unclear. Materials and Methods: In this retrospective study spanning 2 years, the clinical and microbiological characteristics of enterococcal bacteremia among medical ICU patients were evaluated. Results: Of 1325 admissions, 35 with enterococcal bacteremia accounted for 14.8% of positive blood cultures. They were significantly older (P=0.03) and had various co-morbidities. Most had vascular (96.9%) and urinary (85.3%) catheters, and 67.7% were mechanically ventilated. In addition to blood, enterococci were isolated from vascular catheters (8.6%) and other sites (20%), while no focus was identified in 77% of patients. Prior use of broad-spectrum antimicrobials was nearly universal. All isolates tested were sensitive to vancomycin and linezolid. Resistance to ampicillin and gentamicin were 44.7% and 52.6%, respectively. Compared with other medical ICU patients, patients with enterococcal bacteremia had a longer ICU stay (P<0.0001) and a trend toward higher ICU mortality (P=0.08). Conclusions: Enterococcal bacteremia is an important nosocomial infection in the medical ICU, with a predilection for older patients with multiple comorbidities. Its occurrence is associated with a significantly longer ICU stay and a trend to a higher mortality. The choice of antibiotics should be dictated by local susceptibility data.